Analyzing and Measuring Vulnerability: An Approach with Special Reference to Mountain Areas. Issue 1 (April 2017) - Nathan, Dev
The article discusses different approaches to the analysis of vulnerability and argues for the adoption of a capability approach to vulnerability. Vulnerability is related to exposure to hazards and the susceptibility or impact of those events. On the other side are capabilities to cope with and adapt to hazards. In order to retain comparability with the measurement of vulnerability in other geo-ecological zones, the article does not devise a separate index for mountain communities; rather it argues for making sure that mountain-area features of the economy and environment are captured in the variables and indicators. Variables that are to be used in developing an index are divided into three main components of exposure, susceptibility and capabilities, with the latter being subdivided into coping and adaptation.